microRNA profiles in coeliac patients distinguish different clinical phenotypes and are modulated by gliadin peptides in primary duodenal fibroblasts - Vaira, Valentina; Roncoroni, Leda; Barisani, Donatella; Gaudioso, Gabriella; Bosari, Silvano; Bulfamante, Gaetano; Doneda, Luisa; Conte, Dario; Tomba, Carolina; Bardella, Maria Teresa; Ferrero, Stefano; Locatelli, Martina; et al. (Clinical science (1979), 2014)
CD (coeliac disease) is a frequent autoimmune disorder of the small bowel, which is characterized by an immunological reaction against gluten and transglutaminase in genetically predisposed subjects. However, the molecular determinants underpinning CD pathogenesis are yet to be fully elucidated and little data are available about the involvement of miRNAs (microRNAs) in CD. In the present study, the duodenal mucosa miRNA expression was profiled in adult untreated CD presenting with a classic phenotype or iron-deficiency anaemia, treated patients with or without duodenal normalization, and non-CD subjects as controls. Deregulation of seven miRNAs (miR-31-5p, miR-192-3p, miR-194-5p, miR-551a, miR-551b-5p, miR-638 and miR-1290) was determined in a larger series of CD patients with different clinical phenotypes compared with non-CD subjects. These seven microRNAs were then analysed in duodenal fibroblasts obtained from CD patients and incubated with gliadin peptides (13- and 33-mer). The miRNA cluster miR-192/194, involved in matrix remodelling, was deregulated in CD according to the different clinical presentations, and miR-192-3p levels were modulated by gliadin peptides in vitro. In conclusion, the analysis of miRNAs deserves further consideration for its potential use in the treatment and management of CD.